2006
DOI: 10.3354/dao072065
|View full text |Cite
|
Sign up to set email alerts
|

First report on histology and ultrastructure of an intrahemocytic paramyxean parasite (IPP) from tunicate Halocynthia roretzi in Korea

Abstract: In 2004, epizootiological studies were conducted on mass mortalities of tunicates Halocynthia roretzi in Goje, Korea. The clinical characteristics of infected H. roretzi were weakness of the tunic, loss of elasticity, and finally death involving a rupture of the tunic. Histological studies revealed severe hemocyte infiltration in the connective tissue surrounding the intestine and mantle of infected H. roretzi. Hypertrophied eosinophilic hemocytes containing several cytoplasmic vacuoles were observed in the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 7 publications
1
17
0
2
Order By: Relevance
“…Similar granular inclusions are found in tunic cells and in hemocytes of healthy ascidians (Ohtake et al 1994, Hirose et al 2009). In the present study, the hemocytes that are exactly like 'paramyxean-infected cells' in light microscopy reported by Choi et al (2006) were also found in the internal organs of all ascidians observed, irrespective of the health condition of the animals. Therefore, these cells are most likely a type of normal hemocyte of the ascidian, possibly the vacuolated cell (Dan-Sohkawa et al 1995).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Similar granular inclusions are found in tunic cells and in hemocytes of healthy ascidians (Ohtake et al 1994, Hirose et al 2009). In the present study, the hemocytes that are exactly like 'paramyxean-infected cells' in light microscopy reported by Choi et al (2006) were also found in the internal organs of all ascidians observed, irrespective of the health condition of the animals. Therefore, these cells are most likely a type of normal hemocyte of the ascidian, possibly the vacuolated cell (Dan-Sohkawa et al 1995).…”
Section: Discussionsupporting
confidence: 81%
“…In some cases, the clusters of hemocytes were formed in the basal area of the tunic. Among the hemocytes, there were strongly eosinophilic cells, which had large intracellular granules of varying sizes, showing marked resemblance to the cells that were reported to be infected with a paramyxian parasite by Choi et al (2006). These eosinophilic hemocytes were, however, found in all ascidians observed, including apparently healthy animals.…”
Section: Histopathologymentioning
confidence: 82%
See 1 more Smart Citation
“…In the diseased ascidians, the tunics become abnormally thin and soft; the ascidian then dies when the tunic tears. Several attempts have been made to identify the causative agent, and the pathogenic organism of the disease has recently been identified (Jung et al 2001, Choi et al 2006, Azumi et al 2007a,b, Hirose et al 2009, Kitamura et al 2010. Kumagai et al (2010) induced experimental infections by incubating healthy individuals with pieces of softened tunics and found flagellates in the softened tunic.…”
Section: Introductionmentioning
confidence: 99%
“…Due to low fiber density, the tunics become thin and soft and finally rupture leading to leakage of internal tissues and death [6][7][8][9]. Breakdown of the tunics is mediated by a metalloprotease enzyme secreted by A. hoyamushi [10].…”
Section: Introductionmentioning
confidence: 99%